Cardiac and Pulmonary Vascular Remodeling in Endurance Open Water Swimmers Assessed by Cardiac Magnetic Resonance: Impact of Sex and Sport Discipline - Martínez, Vanessa; Sanz-de la Garza, María; Domenech-Ximenos, Blanca; Fernández, César; García-Alvarez, Ana; Prat-González, Susanna; Yanguas, Carles; Sitges, Marta (Frontiers in Cardiovascular Medicine, 2021)
Background: The cardiac response to endurance exercise has been studied previously, and recent reports have described the extension of this remodeling to the pulmonary vasculature. However, these reports have focused primarily on land-based sports and few data are available on exercise-induced cardio-pulmonary adaptation in swimming. Nor has the impact of sex on this exercise-induced cardio-pulmonary remodeling been studied in depth. The main aim of our study was to evaluate cardiac and pulmonary circulation remodeling in endurance swimmers. Among the secondary objectives, we evaluate the impact of sex and endurance sport discipline on this cardio-pulmonary remodeling promoted by exercise training. Methods: Resting cardiovascular magnetic resonance imaging was performed in 30 healthy well-trained endurance swimmers (83.3% male) and in 19 terrestrial endurance athletes (79% male) to assess biventricular dimensions and function. Pulmonary artery dimensions and flow as well as estimates of pulmonary vascular resistance (PVR) were also evaluated. Results: In relation to the reference parameters for the non-athletic population, male endurance swimmers had larger biventricular and pulmonary artery size (7.41.0 vs 5.91.1 cm2, p<0.001) with lower biventricular ejection fraction (EF) (left ventricular (LV) EF: 58 4.4 vs 67  4.5 %, p< 0.001; right ventricular (RV) EF: 60 4 vs 66 6 %, p< 0.001), LV end-diastolic volume (EDV): 106  11 vs 80 9 ml/m2, p<0.001; RV EDV: 101  14 vs 83 12 ml/m2, p< 0.001). Significantly larger LV volume and lower LV EF were also observed in female swimmers (LV EF: 60 5.3 vs 67  4.6 %, p= 0.003; LV EDV: 90  17.6 vs 75 8.7 ml/m2, p=0.002). Compared to terrestrial endurance athletes, swimmers showed increased LV indexed mass (75.0  12.8 vs 61.5  10.0 g/m2, p <0.001). The two groups of endurance athletes had similar pulmonary artery remodeling. Conclusions: Cardiac response to endurance swimming training implies an adaptation of both ventricular and pulmonary vasculature, as in the case of terrestrial endurance athletes. Cardio-pulmonary remodeling seems to be less extensive in female than in male swimmers.